Oxytocin receptor binding sites in the periphery of the neonatal mouse - Greenwood, Maria A. (PLoS One, 2017)
Oxytocin (OXT) is a pleiotropic regulator of physiology and behavior. An emerging body of evidence demonstrates a role for OXT in the transition to postnatal life of the infant. To identify potential sites of OXT action via the OXT receptor (OXTR) in the newborn mouse, we performed receptor autoradiography on 20 μm sagittal sections of whole postnatal day 0 male and female mice on a C57BL/6J background using the (125)iodinated ornithine vasotocin analog ([(125)I]-OVTA) radioligand. A competitive binding assay on both wild-type (WT) and OXTR knockout (OXTR KO) tissue was used to assess the selectivity of [(125)I]-OVTA for neonatal OXTR. Radioactive ligand (0.05 nM [(125)I]-OVTA) was competed against concentrations of 0 nM, 10 nM, and 1000 nM excess unlabeled OXT. Autoradiographs demonstrated the high selectivity of the radioligand for infant peripheral OXTR. Specific ligand binding activity for OXTR was observed in the oronasal cavity, the eye, whisker pads, adrenal gland, and anogenital region in the neonatal OXTR WT mouse, but was absent in neonatal OXTR KO. Nonspecific binding was observed in areas with a high lipid content such as the scapular brown adipose tissue and the liver: in these regions, binding was present in both OXTR WT and KO mice, and could not be competed away with OXT in either WT or KO mice. Collectively, these data confirm novel OXT targets in the periphery of the neonate. These peripheral OXTR sites, coupled with the immaturity of the neonate’s own OXT system, suggest a role for exogenous OXT in modulating peripheral physiology and development.